Mitigating Nitrogen Emissions From Dairy Farming Systems in China - Fang, Qunchao; Ma, Yifei; Zhang, Xiaoying; Wei, Sha; Hou, Yong (Frontiers in Sustainable Food Systems, 2020)
Dairy farming intensification results from the increasing demand for dairy products being met by increasing livestock populations, which places huge pressure on resources and the environment due to poor manure management. In this study, we first quantify the nitrogen (N) flows of two typical dairy manure management systems: “Ganqingfen” system and slurry-based system, based on a substance (N) flow analysis method. Second, the effects of ammonia (NH3) abatement technologies on N recycling efficiency (NRE) and N losses are evaluated for the two systems through a scenario analysis. Furthermore, we explore the mitigation potential of integrated crop and dairy production systems using a scenario analysis of a concatenation of mitigation techniques. The results indicate that the ratio of returned manure N in the “Ganqingfen” and slurry-based manure systems are 32 and 34% of feed N, respectively. N losses from manure management are 56.8–59.5% of total N excretion, of which approximately 50% is emitted as NH3. The scenario analysis indicates that implementation of single or combined NH3 abatement measures can reduce NH3 emissions by 2–56%, whereas nitrous oxide emissions (N2O) can increase depending on the specific measures. Total losses can be reduced from 80.4–83.5 kg N·head−1 to 49.2–55.7 kg N·head−1. Regarding integrated crop and dairy production systems, as the level of scenario optimization improves, resource use (e.g., land use and chemical fertilizer use) and N losses (particularly NH3 emissions) are decreased, while the NRE improves. The results of this study provide insights into the N flow and losses of typical dairy manure management systems in China, as well as effective measures toward the sustainable development of integrated crop and livestock production systems.